Advances in data science : third international conference on intelligent information technologies, ICIIT 2018, Chennai, India, December 11-14, 2018, proceedings (Communications in computer and information science / editors Phoebe Chen [y otros seis], 2019)
This book constitutes the thoroughly refereed post-conference proceedings of the Third International Conference on Advances in Data Science, ICIIT 2018, held in Chennai, India, in December 2018. The 11 full papers along with 4 short papers presented were carefully reviewed and selected from 74 submissions.The papers are organized in topical sections on data science foundations, data management and processing technologies, data analytics and its applications.